PEMBELAJARAN INTEGRASI SENI: STUDI KASUS PADA PELATIHAN GURU-GURU SENI BUDAYA - Rin Surtantini (Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
The current case study aims at describing arts integration approach through the intertwined learning materials of theatre and music in the process of an online training program for arts teachers conducted by BBPPMPV Seni dan Budaya in 2020. Arts integration is an approach that blends content and skills from one arts element with another arts element (music, visual arts, dance, or theater), or with another academic subject. The case study focuses on two research questions, namely (1) How are the design of theater and music learning materials constructed through arts integration approach in an arts teacher training program? and (2) How do teacher trainees describe their theater and music learning experiences through arts integration approach? Qualitative data gathered from a sequence of learning process observation, documentation of participants’ assignment results, reflection process, and results of participants’ work. The results of the study demonstrate that (1) theater and music learning materials through arts integration approach were designed using the linkage factor of the two arts elements which were subsequently taught intertwiningly, and (2) the integration of two arts elements was described by the teacher trainees as a brand-new, engaging, and demanding learning experience which may eventually be an alternative approach they may possibly adopt for the online arts learning in public schools during pandemic time.